A rare nonsynonymous variant in the lipid metabolic gene HELZ2 related to primary biliary cirrhosis in Chinese Han. Issue 1 (December 2016) - Li, Ping; Lu, Guanting; Wang, Li; Cui, Ying; Wu, Ziyan; Chen, Si; Li, Jing; Wen, Xiaoting; Zhang, Haoze; Mu, Shijie; Zhang, Fengchun; Li, Yongzhe
Abstract Background Several genome-wide association studies of primary biliary cirrhosis (PBC) in European and Japanese origins have shown significant association of dozens of genetic loci contributive to the susceptibility of PBC. Most of the loci were related to immune response pathway. In this study, we tested whether the lipid metabolic gene HELZ2 was associated with the pathogenesis of PBC. Methods In 586 PBC cases (358 in case 1 group and 201 in case 2 group) and 726 healthy controls of Chinese Han, six nonsynonymous SNPs were genotyped by MassArray iPLEX. The same control were used for the two groups of PBC cases. Allele frequencies were calculated by χ2 test based on 2 × 2 contingency tables. All data were analyzed using the PLINK tool set. The odds ratio (OR) and 95 % confidence interval (95 % CI) were calculated, andp values (corrected for multiple testing by Bonferroni adjustment) less than 0.05 were considered statistically significant. Results The A allele of rs79267778 was significantly associated with PBC (ORcombined  = 4.204 [1.670–10.582], p combined  = 1.87E−04). It changed the amino acid at position 1904 (NM_001037335) from Threonine (ACG) to Methionine (ATG). This site was highly conserved in mammals and predicted to be POSSIBLY DAMAGING with a score of 0.469 by PolyPhen-2. It's further predicted that T1904 M could INCREASE the protein stability with a confidence at 25.18 % under the condition of pH 7.0 and 37 °C. Conclusion The result was the first time to show evidence of the lipid metabolic gene HELZ2 related to autoimmune disease, at least in PBC of Chinese Han.